You can't always sequence your way out of a tight spot: Next‐generation sequencing holds great promise for pathogen detection, but the devil is in the details. (22nd November 2018) - Treangen, Todd J; Pop, Mihai
Abstract : While DNA sequencing is increasingly being used as a diagnostic tool, targeted assays, culture and other isolation techniques remain a critical component in effective diagnostic workflows.